Role of potassium conductance in mechanisms of exrtacellular atp impact on the contractive activity of vascular smooth muscle cells - S. N. Orlov; L. V. Smagliy; S. V. Gusakova; V. S. Rydchenko; Yu. G. Birulina; A. N. Baikov; V. N. Vasiliyev; G. A. Sukhanova; T. S. Fedorova; T. V. Lasukova (Бюллетень сибирской медицины, 2017)
The purpose of this work is to study the influence of extracellular ATP (adenosine-3-phosphate), which is an activator of purinergic receptors, on contractive activity of rat aortic ring segments precontracted by α1-adrenoreceptors activation with phenylephrine and evaluate the impact of potassium channels of plasma membrane on mechanisms of ATP activity.Material and methods. Contractive activity of vascular smooth muscle cells was studied using the method of Organ Bath Myography applied to the thoracic aorta segments in male Wistar rats both with intact and removed endothelium. ATP (1–1000 mM) produced a dose-dependent relaxing effect on intact and endothelium-denuded segments precontracted with phenilephrine. To assess the impact of potassium channels on mechanisms of ATP activity we used tetraethylammonium (10 mM), a nonselective potassium-channel blocker, glibenclamide (10 mM), the blocker of ATP-sensitive potassium channels and 4-aminopiridine, a blocker of voltage-gated potassium channels.Conclusion. Our study has shown that the impact of ATP on segments with intact endothelium depends on the ATP-sensitive potassium channels whereas the impact of ATP on endothelium-denuded aortic segments depends on both ATP-sensitive and voltage-gated potassium channels.